Pengaruh Harga Dan Kualitas Pelayanan Islami Terhadap Kepuasan Pelanggan Pada Bengkel Anugrah Motor - Arum, Dwi Purnama; Suryaningsih, Sri Abidah (GERASI INSAN NUSANTARA, 2025)
This study aims to identify the influence of prices and Islamic service quality on customer satisfaction at Anugah Motor workshop. This study used a quantitative method with regression analysis using the SPSS 25 version. The instrument used questionnaires and they were distributed to 100 respondents. The determination of the respondents used a purpose sampling technique. The distribution of the questionnaire was carried out both online and offline. Respondents' answers were measured using a Likert scale. The results of the analysis showed that partially, the price variable did not have a positive and significant influence on customer satisfaction. Besides, the Islamic service quality variable partially had a positive and significant influence on customer satisfaction. Simultaneously, the price and Islamic service quality variables had a positive and significant influence on customer satisfaction